Electromagnetic Wave Scattering on Nonspherical Particles Basic Methodology and Simulations - Rother, Tom. (Springer Series in Optical Sciences, 2009)
This book gives a detailed overview of the theory of electromagnetic wave scattering on single, homogeneous, but nonspherical particles. A related Greens function formalism is systematically developed which provides a powerful mathematical basis not only for the development of numerical approaches but also to discuss those general aspects like symmetry, unitarity, and the validity of Rayleighs hypothesis. Example simulations are performed in order to demonstrate the usefulness of the developed formalism as well as to introduce the simulation software which is provided on a CD-ROM with the book.